Label-free surface-enhanced Raman spectroscopy with artificial neural network technique for recognition photoinduced DNA damage - Guselnikova, O; Trelin, A; Skvortsova, A; Ulbrich, P; Postnikov, P; Pershina, A; Sykora, D; Svorcik, V; Lyutakov, O (Biosensors & bioelectronics, 2019)
Taking advantage of surface-enhanced Raman scattering (SERS) methodology with its unique ability to collect abundant intrinsic fingerprint information and noninvasive data acquisition we set up a SERS-based approach for recognition of physically induced DNA damage with further incorporation of artificial neural network (ANN). As a proof-of-concept application, we used the DNA molecules, where the one oligonucleotide (OND) was grafted to the plasmonic surface while complimentary OND was exposed to UV illumination with various exposure doses and further hybridized with the grafted counterpart. All SERS spectra of entrapped DNA were collected by several operators using the portable spectrometer, without any optimization of measurements procedure (e.g., optimization of acquisition time, laser intensity, finding of optimal place on substrate, manual baseline correction, etc.) which usually takes a significant amount of operator's time. The SERS spectra were employed as input data for ANN training, and the performance of the system was verified by predicting the class labels for SERS validation data, using a spectra dataset, which has not been involved in the training process. During that phase, accuracy higher than 98% was achieved with a level of confidence exceeding 95%. It should be noted that utilization of the proposed functional-SERS/ANN approach allows identifying even the minor DNA damage, almost invisible by control measurements, performed with common analytical procedures. Moreover, we introduce the advanced ANN design, which allows not only classifying the samples but also providing the ANN analysis feedback, which associates the spectral changes and chemical transformations of DNA structure.
Keywords: SERS; poškození DNA; Gold; Photo-damage; DNA Damage; neuronové sítě; Spectrum Analysis, Raman; Ramanova spektroskopie; biosenzitivní techniky; Neural Networks, Computer; zlato; Artificial neural network; Detection and recognition; Biosensing Techniques; kovové nanočástice; Metal Nanoparticles; DNA; Oligonucleotides; oligonukleotidy